PENGGUNAAN MODEL ROLE PLAYING UNTUK PENINGKATAN PEMBELAJARAN BILANGAN BULAT BAGI SISWA KELAS IV SDN 1 LUNDONG - Primasari, Rustiana (KALAM CENDEKIA PGSD KEBUMEN, 2014)
Abstract: The using of Role Playing Model for Improving Integer Learning at Fourth Grade Student Elementary School 1 Lundong. The purpose of this research was to describe the using of Role Playing model for improving Integer learning and find problems with solutions. This research used Classroom Action Research technique. The research was conducted in three cycles, with each cycle consisting the planning, implementation, observation, and reflection. Data was collected by observation, questionnaire, and test. The validity of data used triangulation technique and source method. The results showed that: the using of Role Playing model can improve Integer learning at fourth grade students elementary school 1 Lundong. Keywords: Role Playing Model, Integer, Learning Abstrak: Penggunaan Model Role Playing untuk Peningkatan Pembelajaran Bilangan Bulat bagi Siswa Kelas IV SDN 1 Lundong. Tujuan penelitian ini adalah mendeskripsikan penggunaan model Role Playing dalam meningkatkan pembelajaran bilangan bulat dan menemukan kendala serta solusi. Penelitian ini menggunakan teknik Penelitian Tindakan Kelas. Penelitian dilaksanakan dalam tiga siklus, masing-masing siklus terdiri atas tahap perencanaan, pelaksanaan, observasi, dan refleksi. Pengumpulan data dengan observasi, angket, dan tes. Validitas data menggunakan metode triangulasi teknik dan sumber. Hasil menunjukkan bahwa: penggunaan model Role Playing dapat meningkatkan pembelajaran bilangan bulat bagi siswa kelas IV SDN 1 Lundong.